Strategies for Fabricating Nanogap Single-Crystal Organic Transistors. (25th November 2012) - Alborghetti, S.; Stamenov, P.; Fois, G.; Coey, J. M. D.
Abstract : Nanotechnology is an emerging technology for fabricating nanostructures where at least one dimension is smaller than 100 nm. This paper explains how single-crystal organic transistors of channel length down to just 7 nm can be fabricated without damaging the organic material. Single crystals of C60, rubrene, and pentacene have been chosen in our structures, but the same process can be used for a wide variety of organics. The method combines high-resolution electron-beam lithography and vacuum device assembly with piezo manipulators. As modern devices are typically designed with short semiconducting channel length, this type of fabrication methods allows downscaling of organic electronic devices for research purposes.